Segunda reunión - Betanzos, Jorge; Bobadilla, José Luis; Cano, Juan Carlos; Cázares, Ricardo; Díaz, Jessica; Favela, Tania; García, Iván; Manríquez, Hugo García; García Santamaría, Inti; Guzmán, Pedro; Molina, José (2019)
pág. 25-82